Pengaruh Current Ratio dan Inventory Turnover terhadap Net Profit Margin pada Perusahaan Sektor Makanan dan Minuman tahun 2019 s.d 2023 - Anita Rachman; Rosaidah Permanasari; Eka Budi Yulianti (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2026)
The purpose of this research is to examine the relationship between the food and beverage industry's Net Profit Margin (NPM), the Current Ratio (CR), and Inventory Turnover (ITO) for businesses listed on the Indonesia Stock Exchange from 2019 to 2023. Using secondary data culled from firm financial filings, this research employs a quantitative technique. Using a nonprobability sample approach that relies on the availability of financial reports throughout the research period, this study covers all enterprises in the food and beverage industry as its research population. A total of twenty-one businesses make up the study sample. In order to analyze the data, we utilized SPSS version 26 for multiple linear regression analysis, which was followed by descriptive statistics and classical assumption tests. While Inventory Turnover does have a favorable and substantial influence on Net Profit Margin, the research found that the Current Ratio did not have a meaningful effect at all. At the same time, the Net Profit Margin is heavily influenced by the Current Ratio and Inventory Turnover. With an Adjusted R Squared value of 0.132, we can see that the two independent variables only account for 13.2% of the variance in Net Profit Margin; the remaining variation is due to factors not included in our study. This research shows that, when it comes to boosting profits, inventory management efficiency is more significant than cash on hand. In addition to helping management think about ways to boost the company's bottom line, this research should add to the growing body of knowledge on the topic.